45 Years of Simultaneous Le Fort III and Le Fort I Osteotomies: A Systematic Literature Review. (July 2015) - Brown, Matthew S.; Okada, Haruko; Valiathan, Manish; Lakin, Gregory E.
Objective: To review and collectively summarize our knowledge of simultaneous Le Fort III and Le Fort I osteotomies. Design: A PubMed search using "Le Fort III, " "simultaneous Le Fort III and Le Fort I, " "combined Le Fort III and Le Fort I, " "dual midface, " and "segmental midface" was performed. Articles with relevant abstracts were obtained for formal review. A new case of simultaneous Le Fort III and Le Fort I is presented to describe and discuss specific operative indications and surgical decisions. Results: There were 14 articles that met inclusion criteria with reports of simultaneous Le Fort III and Le Fort I osteotomies. A total of 20 cases were present in the literature. No major complications were reported. We performed combined Le Fort III with Le Fort I osteotomies in a 25-year-old patient with Crouzon syndrome who had undergone a previous Le Fort III at the age of 4 years. The patient tolerated the procedure well, and postoperatively, her exophthalmos and class III malocclusion were corrected. Conclusions: Simultaneous Le Fort III and Le Fort I can correct differential upper and lower midface hypoplasia and is a well-tolerated procedure in the mature facial skeleton. This systematic review improves our understanding of the surgical technique and indications for a procedure that can correct complex midfacial deformities.